Samsung Galaxy Note 3 for dummies - Gookin, Dan (John Wiley & Sons, 2014)
The Samsung Galaxy Note 3 is the latest in Samsung's revolutionary line of phablet devices. But what is a phablet? In Samsung Galaxy Note 3 For Dummies, Dan Gookin explains everything you need to know about your new phone/tablet and describes how to maximize the device's performance—even if you've never owned a smartphone or tablet before! Users will love this book for the in-depth look at this great device from Samsung. From the author who wrote the first For Dummies book back in 1991 comes another funny, friendly users' guide that will help you get the most out of your tech investment